PENGGUNAAN MEDIA KARTU REMI KREATIF UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA DI KELAS IVA SDN SIDOTOPO VIII / 55 KECAMATAN SEMAMPIR KOTA SURABAYA - Riski, ; Suryanti, (Pendidikan Sekolah Dasar, 2010)
The purpose of this research to determine whether the use of creative cards can enhance science learning outcomes of students in class VIII SIDOTOPO SDN IVA / 55 Surabaya. This research was conducted in two cycles and each cycle there are several stages, namely planning, action, execution, observation and reflection. In the planning phase, researchers conducted a preparation of learning. In action phase, researchers conducted a teach by using creative media cards. In the observation phase, the researcher with the observer observations on learning took place then analyze the findings in the learning. For the reflection phase, researchers look for weaknesses that occur in learning and then becomes the reference for the second cycle. When the learning process took place both in cycle I and cycle II shows that students are very interested. This is indicated by the responses of students who expressed very pleased to learning. Also the activities of students who demonstrate a positive attitude as the students are very enthusiastic in participating in learning. While in student achievement for the cycle I got the average 77.97 but students completeness are only 68, 57% of the number of students. This condition has not met the standards then it will be continue with the second cycle. In this second cycle the average student gets 85.25 and completeness is 94.29%. So in this second cycle researchers have found that the research meets the standards set by the researcher